Pemodelan Arsitektur Enterprise Menggunakan Standar Togaf di SPBE Kabupaten Parigi Moutong: Enterprise Architecture Modeling Using Togaf Standards at SPBE Parigi Moutong Regency - Pramadinda, Alda Nur; Dwiwijaya, Kadek Agus; Syahrullah, Syahrullah; Lamasitudju, Chairunnisa Ar.; Pusadan, Yazdi (Technomedia Journal, 2025)
The rapid advancement of technology has raised public expectations for easy access to government services and information. In response, the Parigi Moutong District Government has implemented the Electronic-Based Government System (SPBE) with an SPBE index of 2.68, indicating that the system has been well implemented. This study employs the Enterprise Architecture (EA)methodology, based on the TOGAF ADM, with a focus on the infrastructure domain to enhance efficiency, security, and integration within SPBE. The study involves the stages of preparation, data collection, analysis, design, finalization, and validation. The identified gap is that, despite the successful implementation of SPBE, the integration of modern technologies such as AI and blockchain to strengthen security and efficiency has not yet been fully optimized. The novelty of this research lies in the integration of advanced technologies in the Enterprise Architecture blueprint for SPBE, as well as the implementation of pilot testing to evaluate the alignment of the application with real-world conditions. The research aims to develop a comprehensive blueprint offering infrastructure improvement solutions for the Parigi Moutong District Government. The results show that TOGAF ADM successfully improves system integration, bureaucratic efficiency, and public service quality. The conclusion emphasizes the importance of adjusting technology to suit local conditions and needs when applying it to other regions.